Damage mechanics of composite laminates subjected to cyclic flexual load - Koloor, Seyed Saeid Rahimian (2009)
Composite laminates are one of the advanced materials were faced problems to analysis mechanism of damage. The purpose of this study is to develop and validate damage mechanics model for composite laminate's failure and to establish the mechanics of carbon fiber reinforce polymer (CFRP) composite's failure model under flexural fatigue load. The processes of evaluating damage mechanism are to observe its initiation as well as propagation in composite laminates. Three additional cases of static loading were investigated to ensure accuracy of the results of experiment and simulation. The three cases are; a composite laminated beam under tension; a composite laminated plate with a hole at the middle of specimen under tension and a composite laminated beam under bending load. Delamination was focused as the main reason of damage which occurs in macro-mechanics level of composite laminates besides other types of damages have effect in composite laminate's failure. Simulations have been conducted using finite element method. Ye’s delamination criterion was used to develop a new criterion for predicting onset of delamination in composite laminates and power law criterion was used to develop a new principle to predict the propagation of delamination as well. The comparison of experimental and simulation results showed good accuracy indicating, however, the applicability and reliability of this method in delamination of composite laminates.